1971
DOI: 10.1002/macp.1971.021470110
|View full text |Cite
|
Sign up to set email alerts
|

Polyamides from unsaturated acids IV. Polyfumaramides from methyl‐substituted fumaric acids

Abstract: S UMlM A R Y :Unsaturated polyamides from methyl-fumaric (2-methyl-fumaric and 2.3-dimethylfumaric) acid dichlorides and diamines, i.e. 1.6-hexamethylenediamine, 1.10-decamethylenediamine, rn-xylylenediamine, piperazine and trans-2.5-dimethylpiperazine were synthesized by low-temperature polycondensation.The polymer structures and properties were investigated by IR, X-ray, NMR, DSC, and TGA analyses.All polyamides were found t o be soluble in several volatile organic solvents : furthermore unlike polyamides de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…While there were no peaks in DSC thermograms, the POM observation in Figure revealed that the polyamides melted and turned clear after heating to above 150 °C. It has been reported that polyamides consisting of m XDA exhibited similar melting‐like behavior which was caused by glass transition . X‐ray diffractograms of the polyamides are shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…While there were no peaks in DSC thermograms, the POM observation in Figure revealed that the polyamides melted and turned clear after heating to above 150 °C. It has been reported that polyamides consisting of m XDA exhibited similar melting‐like behavior which was caused by glass transition . X‐ray diffractograms of the polyamides are shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…Recently MORTILLARO et aZ. [6][7][8] reported a systematic investigation on the synthesis and the properties of polyfumaramides. We thought it interesting t o synthesize and characterize some polyamides derived from aliphatic dicarboxylic acids having one or more double bonds in the chain such as trans-3-hexene-1.6-dioic(3-HD), trans-4-octen-1.8-dioic(4-OD), trans,trans-2.6-octadien-l.8-dioic(2.6-ODD), and trans,trans-3.7-deca-dien-1.10-dioic acid (3.7-DDD).…”
Section: Introductionmentioning
confidence: 99%